Potencial bioativo de extratos obtidos a partir do resíduo industrial do café torrado utilizando a técnica de ultrassom assistida - Andrade, Sonja de França (2022)
The coffee bean is an agricultural product that makes one of the most consumed beverages and appreciated worldwide both for its aroma and its flavor. Brazil is the world's largest producer of coffee and, as a result, large amounts of agro-industrial residues are obtained during its processing, which are not used because they do not have high commercial value. This work aimed to optimize the process of extracting polyphenolic compounds from industrial coffee residue using an assisted ultrasound technique. In the experiments, the ethanol concentration, liquid/solid ratio and extraction time were varied through the central composite rotational design. The extracts obtained were analyzed to total phenolics and total flavonoids compounds, antioxidant activity by DPPH, FRAP and ABTS methods and antimicrobial activity. Maximum extraction of total phenolics compounds can be obtained when ethanol concentration between 27 and 50%, extraction time between 20 and 35 min and liquid/solid ratio between 42 and 50.00 mL/g were used. For the extraction of total flavonoids, maximum values can be obtained when ethanol concentration between 20 and 27%, liquid/solid ratio between 10 mL/g to 12 mL/g and 48 mL/g to 50 mL/g and extraction times between 20 and 120 min were used. The antioxidant activity was maximum when liquid/solid ratio between 41 and 48 mL/g, extraction time between 115 and 120 min and ethanol concentration between 35% and 46% were used. The antibacterial activity of the extracts was analyzed in vitro. Gram-negative bacteria were sensitive to the extracts, being Pseudomonas aeruginosa, that showed greater sensitivity to more extracts followed by Serratia marcescens and Escherichia coli bacteria. Among the gram-positive bacteria, Staphylococcus aureus was sensitive. The extraction of compounds from the industrial residue of coffee by the assisted ultrasound technique was optimized, demonstrating the potential of the extracts to be used in future applications as a source of bioactive compounds.